Intrafamily resource allocations: a dynamic model of birth weight - Emilia Del Bono; John Ermisch; Marco Francesconi (University of Essex, Institute for Social and Economic Research (ISER), 2008)
This paper estimates a model of dynamic intrahousehold investment behavior which incor-porates family xed eects and child endowment heterogeneity. This framework is applied to large American and British survey data on birth outcomes, with focus on the eects of antenatal parental smoking and maternal labor supply net of other maternal behavior and child characteristics. We nd that maternal smoking during pregnancy reduces birth weight and fetal growth, while paternal smoking has virtually no eect. Mothers work interruptions of up to two months before birth have a positive eect on birth outcomes, especially among British children. Parental behavior appears to respond to permanent family-specic unobservables and to child idiosyncratic endowments in a way that sug- gests that parents have equal concerns, rather than eciency motives, in allocating their prenatal inputs across children. Evidence of equal concerns emerges also from the analysis of breastfeeding decisions, although the eects in this case are weaker.
Keywords: 330